2015
DOI: 10.1021/acscatal.5b00820
|View full text |Cite
|
Sign up to set email alerts
|

Progression of Diiminopyridines: From Single Application to Catalytic Versatility

Abstract: Diiminopyridyl metal complexes, first characterized several decades ago, found practical application in 1998 when they were used as precatalysts in coordinative ethylene polymerization. This discovery contributed to the so-called postmetallocene revolution and triggered the large-scale experimental and theoretical research aimed at understanding diversified diiminopyridine chemistry. The results of this quest, some of which were intriguing and difficult to anticipate, are discussed and summarized in the curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
149
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 195 publications
(172 citation statements)
references
References 168 publications
3
149
0
2
Order By: Relevance
“…For example, i) what relationship between the chelating ligand and the metal determines the polymer properties produced, 22 ii) what factors, either electronic, steric or both, are responsible for generating branched polymers, 1,4,5,6 iii) why do Fe and Co precatalysts tend to give polymers with uniquely vinyl end groups. 2d,10,23 Bearing in mind these questions, 1,13,24 we postulate a mechanistic pathway that accounts for both the terminal and non-terminal double bonds identified in the polymers found in this study (Scheme 2).…”
Section: Mechanistic Implicationsmentioning
confidence: 99%
“…For example, i) what relationship between the chelating ligand and the metal determines the polymer properties produced, 22 ii) what factors, either electronic, steric or both, are responsible for generating branched polymers, 1,4,5,6 iii) why do Fe and Co precatalysts tend to give polymers with uniquely vinyl end groups. 2d,10,23 Bearing in mind these questions, 1,13,24 we postulate a mechanistic pathway that accounts for both the terminal and non-terminal double bonds identified in the polymers found in this study (Scheme 2).…”
Section: Mechanistic Implicationsmentioning
confidence: 99%
“…Collectively, these discoveries have help create a new era in catalytic olefin polymerization that continues apace to this day. Numerous review articles have highlighted the progress in late transition metal pre-catalyst development and its influence on the resulting polyolefinic products [3][4][5][15][16][17][18]. In addition a range of feature articles and book chapters have also focused on iron-and cobalt-based systems [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…To address this, several recent reports have shown that the thermal stability of Fe‐ and Co‐based catalysts may be enhanced using various ligand‐tuning‐based strategies. Many of those recent reports are discussed below, while a more comprehensive review can be found in the literature …”
Section: Thermally Robust Fe‐ and Co‐based Catalystsmentioning
confidence: 99%
“…). These catalysts are most commonly activated using MAO and high activities can be achieved under certain conditions that begin to rival those of commonly employed metallocene‐based catalysts …”
Section: Introductionmentioning
confidence: 99%